PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS MAHASISWA PADA SEKOLAH TINGGI ILMU ADMINISTRASI AMUNTAI - Mohammad Fajar Noorrahman; Nida Urahmah; Rahma Rahma (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aims to analyze the influence of service quality on student loyalty at Sekolah Tinggi Ilmu Administrasi Amuntai and to determine the contribution of service quality in explaining student loyalty. The study employed a quantitative approach with a descriptive survey design. The population consisted of active Sekolah Tinggi Ilmu Administrasi Amuntai students in the 2025/2026 academic year, while the sample was selected through simple random sampling. Data were collected through observation, questionnaires, and documentation. Service quality was measured through tangibles, reliability, responsiveness, assurance, and empathy, whereas student loyalty was measured through cognitive, affective, conative, and action dimensions. Data were analyzed using classical assumption tests, simple linear regression, t-test, Pearson correlation, and coefficient of determination with SPSS. The findings indicate that service quality has a positive and significant influence on student loyalty. The relationship between the variables is strong, and service quality explains more than half of the variation in student loyalty. These findings emphasize the importance of improving service speed, accuracy, fairness, facilities, and responsiveness to strengthen students’ attachment to the institution.